The urboecological factors of Kharkiv Urban space (1654 – 1785) - Нестеренко, Вікторія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
This article is devoted to the significant topic, however, unfortunately, still remains outside the field of the view of researchers - the history of the green space of the Kharkiv city. Using sources of the late XVII - late XVIII century an attempt is made to analyze the anthropogenic pressure on the territory of the city and determine the limit of the population that could live on it. The article is written on the basis of the actor-network theory, which calls to analyze the influence of human and natural actors as symmetrical. This approach allowed us to analyze the collected material from the point of view of the idea of ​​co-evolution of the city and the natural environment. The author analyzed the main urban ecological actors and proved that most of the environmental problems were pestering the inhabitants of the city in the 19th century. Nevertheless, they were unknown in the previous century. The residents’ need for water supply was fully provided thanks to the well system; they existed in almost every yard, and Kharkiv rivers were also full-flowing. A sufficient number of trees protected the city from dust. However, with the development of the city, including through the drainage of significant areas and their subsequent development, the city was exposed to the devastating consequences of the deterioration of its natural condition. All this could have been avoided, as if the officials responsible for the improvement were competent in this matter. Thus, the article calls for further research on the history of green spaces of the city with the aim of formulating the principles of co-evolution of green and man-made spaces.